Военная техника: [12+] / Дыгало В.А.,Кудишин И.В.,Мартынов А. и др. - Мясников А.В. ("Детская энциклопедия РОСМЭН", 2012)
Экземпляры: ДО ст.аб. (20131209) / Инвентарный номер: 50147 / Цена: 103.00 / Авт.знак: В 63 / ББК: 68.8я2